2019
DOI: 10.1007/s10796-019-09945-7
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Governance Institutionalization and the Behavior of Individuals in the Context of Public Organizations

Abstract: This study aims to verify the effects of IT governance (ITG) institutionalization on civil servants' behavior. The general assumption is that ITG institutionalization exerts a positive effect on behavior, provided the ITG legitimation process enhances the perception of organizational justice since transparency and equity increases. Organizational citizenship behavior (OCB) was used to understand individuals' behavior, which describes individuals' voluntary commitment in organizations that is not necessarily pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 58 publications
0
28
0
10
Order By: Relevance
“…Other three papers, after a set of studies in the Brazilian government subnational level, claim that ITG institutionalization exerts a positive effect on behavior since the ITG legitimation process enhances the perception of organizational justice through transparency and equity increase (Wiedenhöft, Luciano, & Macadar, 2016;Wiedenhöft, Luciano, & Pereira, 2019;Wiedenhöft, Luciano, & Porto, 2019). A more recent research showed that when OCB levels are higher, ITG is more easily perceived as effective (Wiedenhöft, Luciano, & Pereira, 2019). The authors claim that a reason for it is the probability that the predisposition to adopt ITG mechanisms increases the governance process' changes, which the organization understood as significant.…”
Section: It Governance Behavioral Approachrelated Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Other three papers, after a set of studies in the Brazilian government subnational level, claim that ITG institutionalization exerts a positive effect on behavior since the ITG legitimation process enhances the perception of organizational justice through transparency and equity increase (Wiedenhöft, Luciano, & Macadar, 2016;Wiedenhöft, Luciano, & Pereira, 2019;Wiedenhöft, Luciano, & Porto, 2019). A more recent research showed that when OCB levels are higher, ITG is more easily perceived as effective (Wiedenhöft, Luciano, & Pereira, 2019). The authors claim that a reason for it is the probability that the predisposition to adopt ITG mechanisms increases the governance process' changes, which the organization understood as significant.…”
Section: It Governance Behavioral Approachrelated Workmentioning
confidence: 99%
“…ITG institutionalization model exerts a positive effect on the consciousness behavior since the relationship mechanisms can make employees aware of the importance of the correct use and preservation of IT resources (Wiedenhöft, Luciano, & Pereira, 2019). Consequently, individuals can more spontaneously contribute to the increase of ITG maturity, since ITG control and feedback mechanisms lead them to be more disciplined and sensitive to organizational issues (Teo, Manaf, & Choong, 2013).…”
Section: Theoretical-empirical Model Theoretical-empirical Modelmentioning
confidence: 99%
See 3 more Smart Citations